Co.lony, student eco hub / Raja Nur Awadah Raja Anuar ... [et al.] - Raja Anuar, Raja Nur Awadah; Kamil Adli, Batrisyia Nur Adlina; Muhammad Nazr, Nur Aliya Maisara; Mohamed, Abdul Hamid (2024)
The Co.lony, Student Eco Hub showcases a fusion of materials, marrying timber and glass to form an architectural marvel. Drawing inspiration from the intricate structure of honeycombs, this design embodies a unique fusion of tradition and innovation in architectural and interior design. By seamlessly blending conventional elements with cutting-edge techniques, this project aims to create visually captivating and structurally robust structures. The focal point of this design is the amalgamation of hexagonal shapes, glass, and wood within timber-based constructions, with a deliberate emphasis on harmonising these materials to achieve a harmonious blend of aesthetics and functionality. Central to this fusion concept are honeycomb structures, renowned for their inherent strength despite their lightweight nature. Through the strategic integration of hexagonal panels into timber frameworks, designers have succeeded in reinforcing structural integrity while simultaneously reducing the overall weight of the structures. This approach not only enhances sustainability but also contributes to cost-effectiveness in construction practices. The inclusion of glass elements further elevates the design, infusing a contemporary flair and facilitating the penetration of natural light into the interiors. Whether in the form of transparent or translucent panels, glass components serve to accentuate the beauty of the wood and honeycomb elements, creating a mesmerising interplay of light and colour throughout the space. Wood, with its innate warmth, versatility, and organic allure, stands as the cornerstone material in this fusion timber design. Beyond providing essential structural support, wood imparts a sense of aesthetic charm and tactile appeal, harmonising seamlessly with the sleek modernity of glass and the efficiency of honeycomb structures. In essence, the Co.lony, Student Eco Hub embodies a harmonious convergence of nature-inspired design and innovative construction techniques. Through the fusion of timber, glass, and honeycomb, this project not only delivers striking visual aesthetics but also champions sustainability and efficiency in architectural endeavours.